SMOKING-RELATED LUNG DISEASES - Umurov Erkin O’tkirovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The compounds in cigarettes are harmful to all living organisms. We have all heard that 1 gram of nicotine can kill a horse. Besides the clear health risks, the positive effects of smoking are minimal. There is an occurrence where nicotine has a beneficial effect on the intestinal mucosa. Through circulation, the substance reaches an area that can protect against ulcerative colitis. Nicotine found in cigarette smoke has anti-inflammatory properties. The effect of smoking on blood vessels is negative, but it helps to balance neurotransmitters. This reduces the likelihood of the onset and progression of Alzheimer’s and Parkinson’s diseases. The process of smoking constricts blood vessels, which enhances mental abilities and improves memory, but still negatively affects the heart.